The Effect of Religiosity on Religious tolerance: A Meta-Analysis - Suminta, Rini Risnawita; Ghufron, M. Nur (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2026)
AbstractReligious tolerance is a crucial issue in most parts of the world. Religion is generally seen as tolerant. Religious tolerance plays a crucial role in diverse and multicultural societies by fostering peace, understanding, and respect among individuals with different religious beliefs. Religious tolerance is crucial in fostering harmonious coexistence, social cohesion, and protecting individual freedoms and rights. The aim of this research is to find out whether religiosity has a relationship with tolerance. This type of research is a meta-analysis, which aims to conclude, integrate, and interpret data from previous research, especially sampling error and measurement error. Therefore, it really depends on the main research; he analyzed data using this method should have the same construct and correlation pattern so they are able to be compared to others. This study was conducted quantitatively by reviewing 15 studies from 9 articles between 2020 and 2025, with a combined sample of 5,289. The analysis included corrections for sampling and measurement errors. The results of the analysis indicated that religiosity is correlated with religious tolerance. Moreover, the results of the study indicated that religion can be a tolerance predictor.